Civic Engagement Menggunakan Media Online di Kalangan Anak Muda Kota Padang - Yayuk Lestari (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
Abstract The rapid development of the Internet raises questions about how the Internet contributes to the formation of civic engagement, including issues related to public interest. Internet presence raises concerns increasingly fertile individualist values, especially among young people. This study intended to investigate form of public participation, especially among young people in the city of Padang and how the role of online media (social media) on the participation of young people in issues of public interest. This research is uses qualitative and quantitative methods with interviews, observations, questionnaires as data collection techniques. Social issues, education and health is a major concern young people in the city of Padang, meanwhile political issues are not preference. Political eficacy is the reason for the reluctance to get involved in political issues. Keywords: Civic Engagement, Media Online, Media Consumption, Digital Activism, Kota Padang